Improving the Understanding of Grade IV Students on Multiplication Operation Material Through the Assignment Method at SDS IT Sulthoniyah Sambas - Dewi, Suci Ratna; Nurhayati, Nurhayati (STKIP Singkawang, 2025)
The research aims to improve the understanding of grade IV students through the assignment method in the Mathematics lesson of multiplication operation material. The subject of the study is 30 students in class IV of SDS IT Sulthoniyah Sambas, Sambas District for the 2024/2025 school year. This type of research is classroom action research that is carried out in two learning cycles. The learning cycle consists of 4 stages, namely planning, implementation, observation, and reflection. Based on the results of the research, there is an increase in student understanding in each cycle, namely in cycle I; student activity 45%, student cooperation 55%, student courage 60%, while in cycle II; student activeness 85%, student cooperation 90%, student courage 90%. So it can be concluded that the use of assignment strategies can have a positive effect on the understanding of students in grade IV of SDS IT Sulthoniyah Sambas, Sambas DistrictMeningkatkan Pemahaman Peserta Didik Kelas IV Pada Materi Operasi Perkalian Melalui Metode Penugasan Di SDS IT Sulthoniyah SambasABSTRAKPenelitian bertujuan untuk meningkatkan pemahaman peserta didik kelas IV melalui metode penugasan dalam pelajaran Matematika materi operasi perkalian. Subjek penelitian tersebut adalah peserta didik kelas IV SDS IT Sulthoniyah Sambas, Kecamatan Sambas tahun ajaran 2024/2025 yang berjumlah 30 orang peserta didik. Jenis penelitian tersebut adalah penelitian tindakan kelas yang dilaksanakan dalam dua siklus pembelajaran. Persiklus pembelajaran terdiri atas 4 tahapan, yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Berdasarkan hasil penelitian diperoleh yaitu adanya peningkatan pemahaman siswa disetiap siklus yaitu pada siklus I; keaktifan siswa 45%, kerjasama siswa 55%, keberanian siswa 60%, sedangkan pada siklus II; keaktifan siswa 85%, kerjasama siswa 90%, keberanian siswa 90%. Sehingga dapat disimpulkan bahwa penggunaan strategi penugasan dapat berpengaruh positif terhadap pemahaman peserta didik kelas IV SDS IT Sulthoniyah Sambas Kecamatan Sambas.Kata Kunci :Metode Penugasan; Pelajaran Matematika; Peningkatan Pemahaman